Post a New Question

algebra

posted by .

(2x-6)-(3x-4)=-(-4+x)-4x+6 the answer is 3 but i don't understand how you get it

  • algebra - ,

    (2x-6)-(3x-4)=-(-4+x)-4x+6

    2x -6 -3x + 4 = 4 -x -4x +6

    -x -2 = -5x + 10

    -x +5x -2 = -5x +5x + 10

    4x -2 =10

    4x -2 + 2 = 10 + 2

    4x = 12

    4x/4 = 12/4

    x = 3

  • algebra - ,

    ( 2 x - 6 ) - ( 3 x - 4 ) = - ( - 4 + x ) - 4 x + 6

    2 x - 6 - 3 x - ( - 4 ) = - ( - 4 ) + ( - x ) - 4 x + 6

    2 x - 6 - 3 x + 4 = 4 - x - 4 x + 6

    2 x - 3 x - 6 + 4 = 4 + 6 - x - 4 x

    - x - 2 = 10 - 5 x Add 5 x to both sides

    - x - 2 + 5 x = 10 - 5 x + 5 x

    4 x - 2 = 10 Add 2 to both sides

    4 x - 2 + 2 = 10 + 2

    4 x = 12 Divide both sides by 4

    x = 12 / 4

    x = 3

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question